A Study Of The Genetic Variations In N-Terminus, C-Terminus And Promoter Of Rb1 Gene Among Retinoblastoma Patients In Malaysia - Hashim, Siti Norulhuda Haji Draman @ (2012)
Retinoblastoma (RB) is the most common primary intraocular tumor affecting mainly children under five years of age, with a prevalence of 1 in 15 000 to 20 000 live births. Retinoblastoma is divided into hereditary and sporadic types. It is caused by mutations or changes in RB1 gene, a tumor suppressor gene. The aim of this study is to detect mutations in N-terminus, C-terminus and promoter region of RB1 gene in retinoblastoma patients in Malaysia, as well as its association with staging and laterality of the patients. A total of 68 children with sporadic RB from Hospital Universiti Sains Malaysia (HUSM), Hospital Kuala Lumpur (HKL) and University Malaya Medical Centre (UMMC) and 68 healthy ethnic-matched controls were recruited.